Asseessment of Cost Efficiency of Hospitality Business Case of SYNN - A state-owner Business Unit - Nawazir, Aysa; Nugroho, Anggoro Budi (The Indonesian Journal of Business Administration, 2015)
Abstract  – Financial reforms in government agencies demanding change from the traditional budgeting system towards performance-based budgeting. Financial reforms in the form of the Public Service Agency (PSA) is intended to provide public services such as the provision of goods and / or services which sold without profit orientation and run activities based on the principles of efficiency and productivity. SH University became PSA since 2008 and since then all the faculty and the business unit that lead by SH University follow BLU system. SYNN as a business unit is a facility built to support the development of the University of SH, this business unit provides services to internal and external parties of SH University in the form of provision of accommodation services and hall  rental services based on principles of productivity and efficiency. In running its business SYNN is very much governed by SH University in controlling the use and reporting of its fund. SYNN spend various expenses through several budgeting funds. Some of expenses are not detected thus the actual cost of running the business is not known, hence there is a tendency of overstated profit and difficulty in cost efficiency management. This alarming situation can lead to wrong judgement in making strategic decision. Another alarming financial condition is stagnant growth and tendency in declining sales revenue in the last eight years. Management team and operational staff have not maximized the potential growth proved by low room occupancy rate. By gaining expected potential grow can help contribute more in maximizing shareholders’ and stakeholders’ value.As one of its characteristic, PSA allows flexibility and autonomy in running its operation; flexibility in financial management, flexibility in asset management and goods/asset procurement. However, it is still difficult to apply by SYNN. As a business unit that is managed by the University, SYNN is still treated equally in doing business with faculty and lack of autonomy to do their business. So the operational team is difficult to move quickly in running the business.This study is expected to provide an overview to the management team, principle and operational team about the actual financial condition of SYNN so that improvements in areas related to  decline in productivity and efficiency can be done. Recommendations resulting from this study is expected to improve the performance of the financial sector in particular and increasing SYNN overall business growth in the future. The study also outlines recommendations for improvement and implementation plan.Keywords: Hospitality Business, Public Service Agency, Revenue, Improvement, Cost, Efficiency